The Chromosomes of Birds during Meiosis - Pigozzi, Maria Ines (2017)
The cytological analysis of meiotic chromosomes is an exceptional tool to approach complex processes such as synapsis and recombination during the division. Chromosome studies of meiosis have been especially valuable in birds, where naturally occurring mutants or experimental knock-out animals are not available to fully investigate the basic mechanisms of major meiotic events. This review highlights the main contributions of synaptonemal complex and lampbrush chromosome research to the current knowledge of avian meiosis, with special emphasis on the organization of chromosomes during prophase I, the impact of chromosome rearrangements during meiosis, and distinctive features of the ZW pair.